Regime hidrológico de duas microbacias contíguas: um comparativo entre uso urbano e rural - Horn, João Francisco Carlexo (2012)
The human action induces changes in basins natural runoff. Flooding may become more intense, there may be more immediate and prolonged droughts, an accelerated erosion process and water quality tends to deteriorate. Thus, this work exposes the need to know the impact in the runoff caused by the use change and land use with emphasis on urban space. So, this study aims to evaluate the differences in the runoff between two contiguous watersheds and with the same area: one being use predominantly agricultural and the other with primarily urban use. For this, it was necessary to evaluate the urbanization influence on the hydrologic regime through the water balance, using two small small watershed, one with 54% of its urbanized area - MU and the other covered with natural grassland and areas used for agriculture - MR, both with the same area of 2.31 km². More specifically, it seeks to quantify some components of water balance variables to estimate water availability and evaluate the small discharges, using monthly retention curves of the studied period. Through the analysis of hydrographs constructed with flow data collected simultaneously each hour in two small watershed of the events that generated the maximum discharges the different variations and the maximum discharge generated in the two small watershed were evaluated using some data collected during the period between January 2011 and October 2011. The global water balance showed that MU had a 5.1 times greater discharge than the MR, and in none of the months monitored MR showed a runoff of more than MU, with emphasis on January and February when it was found the greatest difference in more than 29 times. Analyzing globally the discharges with bigger permanence than 40%, MU presented a volume disposed 7.9 times greater than the MR and in none of months the volume disposed in MR was superior to that of MU, which can be explained by the hypothesis that MR has no underground contribution in its runoff, only in the vadose layer of the soil. Examining the hydrographs it was showed that the MU presents an acceleration in its runoff causing flow oscillations in smaller periods than MR presenting its flow peak up to four hours before the MR, maximum flow rate up to 13,743 L/s, while MR showed a maximum flow of 275 L/s, representing a difference of 66 times in the urbanization effect within the small watershed. Therefore, MU showed a higher runoff volume effect of urbanization within the small watershed and greater water availability than MR, while MR showed a higher loss by evapotranspiration and soil water infiltration than MU during the period of this research.